Schultz–Crock binocular ophthalmoscope. (24th January 2013) - McAllister, Ian L; Keeler, Richard; Burrows, Clive
Abstract The ophthalmoscope, which is an indispensable tool of our profession, is now taken for granted. It is often forgotten that it was only just over 150 years ago that the first binocular ophthalmoscope was invented. The early instruments were not popular for a variety of reasons. Australians Donald Schultz and Gerald Crock played a major role in improving this instrument and developing the modifications that turned it into an everyday tool of all ophthalmologists.